PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA SISWA KELAS IV DALAM PEMBELAJARAN IPAS MATERI WUJUD ZAT DAN PERUBAHANNYA DI SDN 1 LEMAHABANG KULON KABUPATEN CIREBON - Nurfadiyah, Alfina; Sholeh , Abdul; Zulaiha, Fanni (Jurnal Ilmu Pendidikan Dasar (JIPDA), 2025)
Critical thinking skills in fourth-grade students at SDN 1 Lemahabang Kulon, Cirebon Regency, are still low in IPAS learning on the topic of states of matter and their changes. This is because the learning model used by the teacher is not varied enough, causing students to be less careful and focused when reading. One creative and innovative learning model that can be implemented is using the inquiry-based learning model to create an effective and efficient learning environment. This research aims to describe how the inquiry learning model is applied to students’ critical thinking abilities and to determine the effect of the inquiry learning model on the critical thinking abilities of fourth-grade students in IPAS learning on the topic of matter and its changes at SDN 1 Lemahabang Kulon, Cirebon Regency. This type of research is quantitative research using an experimental research method with a one-group pretest-posttest design. The population of the fourth grade at SDN Lemahabang Kulon, Cirebon Regency, is 24 students. The sampling technique used was saturated sampling, so all students were included in the research sample. The research hypotheses are: H1 = There is an influence of the Inquiry Learning Model on critical thinking skills in 4th-grade students in IPAS learning on the topic of states of matter and their changes at SDN 1 Lemahabang Kulon, Cirebon Regency. H0 = There is no influence of the Inquiry Learning Model on critical thinking skills in 4th-grade students in IPAS learning on the topic of states of matter and their changes at SDN 1 Lemahabang Kulon, Cirebon Regency. The results of this study show that the Sig value is 0.001, meaning 0.001 < 0.05, and the pretest average score is 56.4583 while the posttest average score is 84.1667. This means H1 is accepted and H0 is rejected. Therefore, it can be concluded that there is an influence of the inquiry learning model on the thinking ability of fourth-grade students in IPAS learning material on the forms of matter and their changes at SDN 1 Lemahabang Kulon, Cirebon Regency.